A General Analytical Formulation for LCL Filter Design for Grid-Connected PWM-Driven Cascaded H-Bridge Inverters - Giuseppe Schettino; Giuseppe Sorrentino; Gioacchino Scaglione; Claudio Nevoloso; Antonino Oscar Di Tommaso; Rosario Miceli (IEEE Open Journal of Power Electronics, 2024)
This paper proposes a general analytical formulation for LCL filter design for grid-connected PWM-driven cascaded H-bridge inverters. The novelty of this work deals with providing some easy-of-use analytical expressions that allow for properly sizing the filter inductances and capacitance values considering the number of voltage levels, the DC-link voltage, the adopted multicarrier pulse width modulation strategy, and the switching frequency. Although multilevel inverters performance strongly depends on the adopted modulation strategy and switching frequency, a general mathematical formulation that allows for properly sizing the LCL filter by considering such parameters simultaneously is currently missing. The proposed approach is generalized for the most adopted multicarrier pulse width modulation strategies. To validate the proposed approach, an extended investigation analysis is performed by hardware-in-the-loop real-time tests. According to international standards EN50160 and IEEE Std 1547–2018, the voltage total harmonic distortion and current total rated distortion are adopted to evaluate the LCL filter performance. Tests are carried out in several working conditions, defined in terms of provided apparent power and power factor values. Finally, the proposed analytical formulation is adopted to formulate an optimized LCL filter design algorithm that allows for matching the standard requirements without oversizing the filter parameters.